The Implementation of Justice (al-Adl and al-Qisth) in Court Decisions from a Historical–Juridical Perspective - Muh Saad Said Lidinirrahman; Abdul Halim Talli; Zulhas'ari Mustafa (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This article examines the implementation of justice in court decisions from a historical–juridical perspective by analyzing the interrelationship between Islamic law, national law, and international human rights instruments. Justice in the judicial process is understood as a fundamental principle that must be realized from the investigation stage to the execution of court decisions. This study employs a qualitative method with normative-historical and juridical approaches through an analysis of Qur’anic verses, Hadith, the views of classical and contemporary Islamic jurists, as well as statutory regulations and international human rights documents. The findings indicate that Islamic law had established the principles of a fair trial long before the concept was formally recognized in modern legal systems. These principles include legality, the presumption of innocence, judicial independence and impartiality, open court proceedings, equality of the parties, the right to legal representation, the prohibition of undue delay, the right to remain silent, and the prohibition of torture. These principles are consistent with the provisions of the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights. Therefore, the concept of justice in Islamic law has strong relevance to modern judicial systems and can serve as an ethical and juridical foundation for realizing justice that upholds human dignity.